KEY TECHNOLOGICAL SOLUTIONS FROM THE SESAR PROGRAMME TO IMPROVE AIR TRAFFIC SAFETY - Jan LASKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The dynamic development of the air transport market has led to a significant increase in air traffic in a highly fragmented and relatively small European airspace. This situation could, in the near future, render the currently functioning European air traffic management (ATM) system obsolete and incapable of providing the high safety standards demanded by the ICAO and Eurocontrol. Recognizing the urgency in finding a solution to this problem, the EU gas launched the Single European Sky (SES) initiative, along with its technological pillar, the Single European Sky ATM Research (SESAR) programme, which seeks to enhance air traffic safety, support the sustainable development of the air transport system and improve the overall performance of ATM and air navigation services, so that they meet the requirements of all airspace users. This paper presents a selection of the SESAR programme’s key technological solutions, such as approaches based on area navigation (RNAV)/Global Navigation Satellite Systems (GNSS), and the “remote tower” concept, which have been developed to maximize the safety and efficiency of the new European ATM system.